The Missing Style Problem and the Translation of French Erotica into English - Mossop, Brian (Meta, 2017)
In most synonym sets, there is a neutral item that does not belong to any particular style (poor is neutral whereas impecunious and broke are not). In writings about sex, French has a neutral style but English does not. The English translations of two French autobiographies detailing the authors’ sex lives are presented and some of the translators’ strategies are discussed. These two cases are seen against the general background of style options available to translators. A translator’s approach to style can be theorized by comparison to the source text (use an equivalent style, use a different existing style, create a new style, use a default ‘translating style’) or by considering how the translator ‘voices’ the translation (use the voice of the source writer, the imagined future readers, the translator, or some other voice).